The Development of Android-Based Scar Media Differentiated Learning Model Anti Lock Brake System Material Light Vehicle Engineering Competence Class XII Vocational School - Sardi, Sardi; Anis, Samsudin; Rubai Wijaya, Burhan (Journal of Vocational and Career Education, 2023)
The achievement of student competence was still relatively low, one of the causes was the lack of maximum teacher creativity in developing innovative and creative learning media by utilizing digital technology in teaching and learning activities with differentiated learning models. One of the utilization of digital technology was the development of Android-based SCAR on ABS brake system material for class XII Vocational School. The purpose of this research was to improve students' cognitive scores and psychomotor/practical abilities that were abstract. This research applied the R&D (Research and development) method. The research design chosen was the ADDIE model, which consisted of five stages namely Analysis, Design, Development, Implementation, and Evaluation. The unit of analysis of this research was the development of Android-based SCAR. The instruments used in this research were (1) assessment sheet; (2) practicality questionnaire and (3) feasibility questionnaire. The validity of the assessment sheet was obtained from the CVR calculation and reliability using the ICC formula. The validity of the practicality questionnaire used the point biserial correlation coefficient formula, and the reliability of the questionnaire usef the KR20 formula. The validity of the effectiveness questionnaire used rhitung and reliability using Cronbach's Alpha formula. The data analysis used in this research were (1) categorial to determine the level of feasibility; (2) Guttman categorial; and (3) N-Gain and N-Gain difference test using t test. The results showed that the feasibility test of media expert and material expert responses was very feasible, the practicality test was very feasible, while the effectiveness test was quite effective and significant to improve students' cognitive scores and abstract psychomotor/practical abilities.